Analysis of de novo donor-specific HLA-DPB1 antibodies in kidney transplantation - Tang, Chen; Unterrainer, Christian; Fink, Annette; Cinca, Sofia; Ruhenstroth, Andrea; Scherer, Sabine; Morath, Christian; Zeier, Martin; Mehrabi, Arianeb; Süsal, Caner; Tran, Thuong Hien (HLA, 2021)
HLA matching and avoidance of unacceptable mismatches are important aspects in the selection of donors for solid organ transplantation. The impact of HLA-DPB1 incompatibility on the outcomes of kidney transplantation is not fully understood. We investigated a potential effect of mismatching for HLA-DPB1 at allele, eplet, or Terasaki epitope (TerEp) level on the formation of de novo donor-specific antibodies (dnDSA) and also asked whether polymorphisms associated with HLA-DPB1 expression level may influence dnDSA induction. Furthermore, we analyzed the correlation between graft survival and HLA-DPB1 mismatches defined by different approaches. A cohort of 366 patients who received a kidney transplant at the Heidelberg University Hospital, Germany, with availability of pre- and post-transplant HLA antibody results by single antigen testing as well as of donor and recipient HLA-DPB1 high-resolution typing were analyzed retrospectively. Susceptibility to increased HLA-DPB1 expression was predicted by the linked dimorphism rs9277534 A/G of the HLA-DPB1 gene. Neither HLA-DPB1 mismatches at allele, eplet or TerEp level nor exposure to donor's high HLA-DPB1 expression were significantly associated with the risk of developing dnDSA against HLA-DPB1. However, HLA-DPB1 eplet and TerEp mismatches had a significant negative impact on graft survival (p < 0.001 and p = 0.003, respectively). Matching for HLA-DPB1 at epitope instead of allele level appears to have potential to improve graft survival in kidney transplantation.
Gesehen am 08.08.2023